Examining perceptions of American and Omani university students towards ethical behaviour of entrepreneurs and business managers. (15th August 2022) - Ghouse, Suhail M.; Batchelor, John H.; III, Dennis Barber; Alhouli, Areej
This research examines and compares perceptions of Omani university students with those of American business students towards entrepreneurs and business managers. Bucar and Hisrich's (2001) model was used to measure and collect students' perceptions towards ethical behaviours of firm managers and entrepreneurs. T-tests were employed to test statistical significance in the mean scores of Omani and American students. Results showed that Omani students perceive entrepreneurs as more ethical in decision making than managers, following the American sample, but with no significant gender based alterations among them. However, degree of perception among American students was higher than Omani students, being contrary to previous studies. This study contributes to body of literature contextually, firstly by adding Oman (Arab) to existing body of knowledge based on gender, national differences and institutions, and secondly by making comparative study of youth perceptions towards ethical behaviour of entrepreneurs and managers between a developed and a developing country.